Evaluation of relationship between repeat breeding and Fasciola hepatica and hydatid cyst infections in cows in Elazig district of eastern Turkey - Simsek, S.; Risvanli, A.; Utuk, A. E.; Yuksel, M.; Saat, N.; Koroglu, E. (Elsevier Sci Ltd, 2007)
Sera samples from 89 dairy cows with repeat breeding and I I I healthy pregnant dairy cows (controls) from Elazig province of eastern Turkey were tested for presence of Fasciola hepatica and Hydatid cyst antibodies by use of an indirect enzyme linked immunosorbent assay (indirect- ELISA). One hundred and twenty one (60.5%) and 93 (46.5%) cows were found to be positive to F. hepatica and Hydatid cyst antibodies, respectively. Fifty two of 89 cows (58.4%) with a history of repeat breeding were seropositive to F. hepatica, and 43 of 89 (48.3%) were seropositive to Hydatid cyst antibodies. Whereas, seropositivity rates were 62.1% (69/11) for F. hepatica and 45% (50/111) for Hydatid cyst in healthy pregnant cows (control group). There were no statistically relationship between infected and control group (P > 0.05). In conclusion, we could not detect any relationship between repeat breeding and F. hepatica and Hydatid cyst infections in cattle. Crown Copyright (c) 2006 Published by Elsevier Ltd. All rights reserved.
Keywords: repeat breeding; Fasciola hepatica; hydatid cyst; infertility; cow